2023
DOI: 10.3390/ijerph20064931
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Effect of Digital Economy on Carbon Emissions under the Background of “Double Carbon”

Abstract: (1) Background: In light of the global economy’s digitalization and the “double carbon” target constraint, the digital economy is essential to fostering scientific and technological innovation, green growth, and lowering energy emissions. (2) Methods: This paper measures the digital economic index and carbon emission intensity and analyzes their characteristics in spatial and temporal dimensions using 282 Chinese urban panel data by improving various statistical methods of panel data, such as the entropy metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…According to the data in column (4) in Table 6, both the digital economy and the efficiency of capital allocation have an impact on carbon emissions, and the efficiency of capital allocation also plays an intermediary role, but the conclusion is not statistically significant. According to the survey results in column (6), both the digital economy and the efficiency of labor allocation will affect carbon emissions. Nevertheless, the efficiency of labor allocation plays an intermediary role.…”
Section: Intermediary Effect Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data in column (4) in Table 6, both the digital economy and the efficiency of capital allocation have an impact on carbon emissions, and the efficiency of capital allocation also plays an intermediary role, but the conclusion is not statistically significant. According to the survey results in column (6), both the digital economy and the efficiency of labor allocation will affect carbon emissions. Nevertheless, the efficiency of labor allocation plays an intermediary role.…”
Section: Intermediary Effect Analysismentioning
confidence: 99%
“…As a new financial format, the digital economy has continuously improved the level of digitalization, networking and intelligence of the economy and society through the expansion of digital industrialization and industrial digitalization [6]. It not only effectively promotes the high-quality growth and innovation ability of the city, but also shows certain environmental improvement effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ning and Yang [ 41 ], empirically analyzed the impact of DIE on industrial CEE based on the provincial panel data of China, concluding that areas with the high level of DIE had higher CEE, and DIE played a significant role in promoting CEE. Cheng and Qu [ 42 ], using 282 Chinese urban panel data by improving various statistical methods of panel data, examined the extent and mechanism of the DIE’s impact on urban carbon emissions, and showed that DIE could significantly reduce carbon emissions through the rational layout of industrial structures. Furthermore, Ming et al [ 43 ] applied the spatial panel Durbin model and the mediating effect model to empirically investigated the mechanism and influence of the DIE on carbon emission reduction and found that carbon emission reduction could be indirectly affected by the DIE through the transformation of energy structure, showing regional heterogeneity in the effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, it is necessary to improve the audit process of compliance with laws and regulations, and dynamically adjust the compliance strategy of the enterprise by combining the audit results, so that the operation of the enterprise is not negatively affected by the policy changes, and at the same time, through the enhancement of regulatory compliance, the enterprise's sense of social responsibility and brand value can be enhanced. [1] Corporate carbon audit should not only practice the guiding principles in the Opinions, but also continue to explore and optimize them in practice, and feedback them to the policy formulation level to form a closed-loop optimization iterative mechanism. This requires a high degree of professionalism and foresight on the part of the corporate audit department.…”
Section: The Main Task Of "Dual-carbon"mentioning
confidence: 99%